1D Helical Single‐Crystal to 3D Lonsdaleite Single‐Crystal Transformation of Copper(II)‐Based Coordination Polymer: Acetone Fluorescence Sensing and CO2 Gas Separation. Issue 13 (4th April 2019) - Sasikala, Vadivel; Sundar, Jeyaperumal Kalyana; Lakshmi, Muppudathi Anna
Abstract: The temperature‐driven 1D helical single‐crystal (1) to 3D lonsdaleite (2) single‐crystal transformation of copper‐based coordination polymer has been investigated. Powder X‐ray diffraction experiments showed that the phase transitions described for single crystals also occur in the powder samples. The thermal stability of the compounds were studied by Differential Scanning Calorimetric (DSC) and thermal gravimetric (TG) analyses indicates, there is no coordination water molecules were present in the 2 also thermal stability increased. In UV‐Vis absorption spectra, compound 2 has blue shift compared to 1 due to partial decrease in the number of electrons surrounding Cu 2+ ion and the geometry around Cu 2+ center after loss of H2 O. Interestingly both compounds showed the tremendous luminescent enhancement for acetone in the visible region and detection limit of 2 was 4.04x10 −9 M is much better than its threshold limit recommended by WHO. Porous natures of the compounds were analyzed by theoretical and experimentally. BET sorption analyze indicated both crystal phases selectively adsorb CO2 over N2. Therefore, this compounds, promising material for acetone sensor, selective sorption, separation of CO2 from industrial flue gas or the removal of CO2 from natural gas. Abstract : The temperature‐driven 1D helical single‐crystal (1) to 3D lonsdaleite (2) single‐crystal transformation of Cu 2+ based MOFs have been investigated. Interestingly, both compounds showed the tremendous luminescent enhancement for acetone in the visible region. The detection limit of GCuN2 was much better than recommended by WHO. The sorption analyze indicated both crystalline phases selectively adsorb CO2 over N2. Therefore, these compounds are promising materials for dual applications like acetone sensor, selective sorption and separation of CO2 from industrial flue gas.